ISOLASI DAN KARAKTERISASI BAKTERI DARI IKAN FERMENTASI BEKASAM (RASBORA SP.) SERTA EVALUASI POTENSI ANTIBAKTERINYA - M. Rifqi Efendi; Yunita Safitri; Rustini Rustini; Mesa Sukmadani Rusdi (JURNAL FARMASI DAN MAKANAN, 2024)
Bekasam is a traditional fermented fish product. This study aimed to isolate and identify the bacteria involved in the fermentation of Bekasam from Riau and evaluate the antibacterial potential of their ethyl acetate extracts. Bacterial isolation was conducted using the pour plate method with selective media (MRS agar-CaCO3 0.5%). Antibacterial activity was tested against Gram-positive bacteria (Staphylococcus aureus and Enterococcus faecalis) and Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) using the agar diffusion method, with chloramphenicol as a positive control. Four bacterial isolates were identified: Lactobacillus sp1 (BAC1), Lactobacillus sp2 (BAC2), Bacillus sp1 (BAC3), and Bacillus sp2 (BAC4). All ethyl acetate extracts from these isolates demonstrated antibacterial activity. The highest activity was observed from the Lactobacillus sp1 extract against E. coli, with an inhibition zone diameter of 16.1 mm.